EFISIENSI PEMBERIAN PERUPUK TERHADAP SERAPAN LIMBAH CAIR INDUSTRI KARET - Deddy Dharmaji (Fish Scientiae, 2019)
This research was aimed to analyze the ability of perupuk (Phragmites karka Trin) inreducing the element of rubber industrial liquid waste polluters on the scale of the laboratory. The method used was the method of survey. The data from laboratory test were tabulated and analyzed descriptively and the level of efficiency was calculated. Referring to South Kalimantan Governor Regulation Number 36 in 2008, the results showed that, TSS parameters started to be effectively reduced on day 10 (T 1) withclose to 84,33 mg/l (32.53%), BOD5 started to be effectively reduced on day 20 (T 2) with close to 24.00 mg/l (99,29%), and COD started to be effectively reduced on day 20 (T2) with close to 44,65 mg/l (98,90%) due to the levels were already below the value of the Quality Standard Liquid Waste (QSLW). Generally, time retention was best accomplished on day 30 (T3) in reducing liquid waste rubber industry.